The effect of working capital turnover and receivables turnover of return on equity: A case study from cooperative - Muhammad Yamin; Aliah Pratiwi (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2020)
The research aims to determine the influence of working capital turnover, receivables turnover on return on equity (ROE) at Koperasi Pegawai Negeri (KPN)